1 - Reaching Critical Mass in Nigeria’s Telephone Industry - Chuka Onwumechili (Africa Media Review, 2005)
The sudden and rapid growth in access to telephones in Nigeria has certainly raised major questions for tele-communications scholars. Access to telephones in Nigeria had been marginal by the end of the twentieth century with the teledensity rate well below 1:100 for a country of estimated 130 million persons (Ajayi, Salawu and Raji 1999). Today, over 10 million Nigerians have access, improving the teledensity to 13:100 in barely five years! Growth rates are currently over 100 percent per year. What happened? How was the industry turned around? Has critical mass been reached? Has the rate of growth become selfsustaining? This paper explores all the above questions using the theory of critical mass as the framework for analysis. It concludes that a critical mass of users has been built in the urban centers and that access is rapidly approaching the saturation point. In addition, it argues that much more needs to be done in order to achieve similar growth rates in the rural areas.